Sexual reproduction of the reef-building coral Diploria labyrinthiformis(Scleractinia: Faviidae), in the Colombian Caribbean (2004)
Sexual reproduction of the coral Diploria labyrinthiformis was studied for the first time. Monthly histological analyses at the Corales del Rosario National Park (Colombian Caribbean) from May 1997 to April 1998 show that D. labyrinthiformis is a hermaphroditic broadcasting species. It presents an annual gametogenic cycle with a 10-11 month period for gonad investment, in which oogenesis begins in August and ends in May-June. Spermiogenesis is short because sperm cysts were only observed in May tissue samples. In histological collected in May, an average of four mature eggs and six spermatic cysts per fertile mesentery were found. The mean diameter of mature eggs was 297 μm (± 97 SD) and 90 μm (± 33) for spermatic cysts. Rapid maturation of eggs from stage II to stage III coincides with increases in air temperature, high number of solar hours per month, decreases in wind velocity and absence of rainfall. Reproductive effort for D. labyrinthiformis (14.07 mm3/cm2/year) was similar to other Faviidae species. Although gamete release was not observed in the field, the absence of gonads in histological samples in June suggests spawning between May 25 (five days after full moon) and June 24. This event coincides with high air temperature, low number of solar hours per month, low wind velocity, and initiation of the rainy season. The earlier spawning time of this species differs from other species of the same family known for the Caribbean region. Rev. Biol. Trop. 52(4): 859-868. Epub 2005 Jun 24.